Aging and individual differences in rapid two-choice decisions - RATCLIFF, ROGER (2006)
The effects of aging on performance were examined in signal detection, letter discrimination, brightness discrimination, and recognition memory, with each subject tested on all four tasks. Ratcliff's (1978) diffusion model was fit to the data for each subject for each task, and it provided a good account of accuracy and the distributions of correct and error response times. the model's analysis of the components of processing showed that aging had three main effects: the nondecision components of processing were slower and the decision criteria were more conservative for 60- to 74-year-old and 75- to 85-year-old subjects than for college students, but the quality of the evidence on which decisions were based was as good for the older subjects as for college students on some of the tasks. individual differences among subjects in components of processing tended to be preserved across the tasks, as was shown by strong correlations across the tasks in the parameters of the model that represent the components of processing. for example, if the evidence on which a subject's decisions were based was good in one task, it tended to be good in all four tasks.